The effect of budesonide delivered by high-frequency oscillatory ventilation on acute inflammatory response in severe lung injury in adult rabbits - Nemcova, N; Kosutova, P; Kolomaznik, M; Mateffy, S; Turianikova, Z; Calkovska, A; Mikolka, P (Physiological research, 2023)
The inflammation present in acute respiratory distress syndrome (ARDS) and thereby associated injury to the alveolar-capillary membrane and pulmonary surfactant can potentiate respiratory failure. Even considering the high mortality rate of severe ARDS, glucocorticoids appear to be a reasonable treatment option along with an appropriate route of delivery to the distal lung. This study aimed to investigate the effect of budesonide therapy delivered intratracheally by high-frequency oscillatory ventilation (HFOV) on lung function and inflammation in severe ARDS. Adult New Zealand rabbits with respiratory failure (P/F<13.3 kPa) induced by intratracheal instillation of hydrochloric acid (HCl, 3 ml/kg, pH 1.5) followed by high tidal ventilation (VT 20 ml/kg) to mimic ventilator-induced lung injury (VILI) were treated with intratracheal bolus of budesonide (0.25 mg/kg, Pulmicort) delivered by HFOV (frequency 8 Hz, MAP 1 kPa, deltaP 0.9 kPa). Saline instead of HCl without VILI with HFOV delivered air bolus instead of therapy served as healthy control. All animals were subjected to lung-protective ventilation for 4 h, and respiratory parameters were monitored regularly. Postmortem, lung injury, wet-to-dry weight ratio, leukocyte shifts, and levels of cytokines in plasma and lung were evaluated. Budesonide therapy improved the lung function (P/F ratio, oxygenation index, and compliance), decreased the cytokine levels, reduced lung edema and neutrophils influx into the lung, and improved lung architecture in interstitial congestion, hyaline membrane, and atelectasis formation compared to untreated animals. This study indicates that HFOV delivered budesonide effectively ameliorated respiratory function, and attenuated acid-induced lung injury in a rabbit model of severe ARDS.
Keywords: Lung Injury; Animals; poškození plic; Inflammation; cytokiny; Rabbits; Respiratory Distress Syndrome; králíci; zánět; zvířata; Cytokines; Budesonide; syndrom dechové tísně; budesonid; respirační insuficience; Respiratory Insufficiency